Quality of life and mental health status among the caregivers of genetic disease patients in Southern Karnataka, India - Aparna Mohandas; Deepa Bhat; Sunil Kumar D; M.R. Narayana Murthy (Elsevier, 2021)
Objectives: The burden due to genetic diseases and congenital anomalies are on a rise. These diseases have an impact on several implications of life, ranging from economic burden, lifelong dependency and associated social stigma. The present study was conducted to assess the quality of life and mental health status among caregivers of genetic disease patients in Southern Karnataka, India. Methods: This cross sectional study was conducted among 101 caregivers of genetic disease patients attending a tertiary care hospital in Southern Karnataka, India for a period of one and half years. After obtaining consent, sociodemographic data was collected. WHO-BREF and DASS-21 tools were used to assess the quality of life and mental health status, respectively. SPSS V.22 was used for statistical analysis. Quantitative data showing non-parametric distribution was expressed as median, interquartile range. Inferential statistical tests like Mann Whitney U test and Kruskal Wallis test were used. Results: The median quality of life score was 81 with interquartile range of 75-81 in Domain 1(Physical health), 69 with interquartile range of 56-75 in Domain 2(Psychological domain), 75 with interquartile range of 56-75 in Domain 3(Social relationships) and 69 with interquartile range of 63-75 in Domain 4 (Environment). The median score of depression among the participants was 2 with an interquartile range of 0-7, anxiety was 0 and that of stress was 2 with an interquartile range of 0-8. Females had higher depression, anxiety and stress scores. Conclusion: Psychological health, environment and social relationships were affected the most. Awareness, service accessibility along with psychosocial support can help in positive adaptation.